DIFFERENCES IN BURNOUT AMONG NURSES WORKING IN OUTPATIENT, INPATIENT, AND EMERGENCY DEPARTMENT UNITS AT IMANUEL WAY HALIM HOSPITAL - Evryna Sipahutar; Bayu Anggileo Pramesona; Septia Eva Lusina; Rika Lisiswanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Burnout among nurses varies across hospital units, with emotional exhaustion particularly higher in the emergency department due to acute workload. This study compared burnout rates among nurses in the outpatient, inpatient, and emergency departments of Imanuel Way Halim Hospital. Using a comparative cross-sectional design, 115 nurses were selected proportionally from a population of 161 through stratified random sampling. Burnout was measured using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS; 22 items, three dimensions), analyzed using the Kruskal-Wallis test and post-hoc Bonferroni test after normality testing. Results showed a significant difference only in emotional exhaustion (H = 7.559, p = 0.023), with the highest score in ED nurses (mean = 41.00) versus inpatient (34.01) and outpatient (35.89); post-hoc analysis confirmed the inpatient-ER difference (p = 0.006). Depersonalization and personal accomplishment did not differ (p > 0.05). The conclusion emphasizes specific interventions for emotional exhaustion in the ED through staffing adjustments and psychosocial support, addressing unit-specific risks in Indonesian type B hospitals.